Single Switch Flyback PFC Converter for Optimal Efficiency in BLDC Motor Drives - V., Gopalakrishnan; A., Ramachandiran (Journal of Electrical Engineering and Automation, 2025)
This research presents the design and implementation of a single-switch flyback PFC (Power Factor Correction) converter for Brushless DC (BLDC) motor applications. By operating in Discontinuous Conduction Mode (DCM), the converter achieves a power factor exceeding 0.9, improving efficiency and reducing energy losses. The converter provides electrical isolation, ensuring safety while integrating power conversion and power factor correction in a single stage. A lossless snubber circuit is included to mitigate voltage spikes and recycle leakage energy, further enhancing efficiency. Simulation results show the converter delivers 48V and 1A with high efficiency across varying loads. Its compact design reduces component count and manufacturing costs, making it ideal for space-efficient solutions in modern electrical systems. This work demonstrates the potential of single-switch flyback PFC converters in optimizing BLDC motor performance and ensuring reliable power quality.